FAKTOR YANG BERHUBUNGAN DENGAN KETERLAMBATAN RUJUKAN IBU BERSALIN KE RUMAH SAKIT UMUM DAERAH GUNUNG SITOLI KABUPATEN NIAS TAHUN 2014 - Christianty Olivia Zebua; Ria Masniari Lubis; Abdul Jalil Amri Arma (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Gunungsitoli Hospital is a government hospital that became a referral centers in Nias Island. Referred to the maternity hospital, there are many who experience delays. Conducted this study in order to determine the factors associated with maternal referral delay to Gunungsitoli Hospital, in Nias Regency. The kind of this research was observational by the collection method of data was cross sectional. Population is all maternal who were referred to Gunungsitoli Hospital. The number of sample was 19 persons and this research used consecutive as technique sampling. It means that the sample were patients who were coming to the hospital when the research was done. The result of the research got that family decision, fund, and geographic did not have a significant relationship with maternal referral delay to Gunungsitoli Hospital. While the birth attendants factor have a significant relationship with maternal referral delay to Gunungsitoli Hospital by p value = 0,005 (<0,05). Competent birth attendants there are 10 people, which is 8 people (80%) is not too late and 2 (20%) were referred late. While birth attendants who are not competent, ie 1 (11.1%) is not too late and 8 (88.9%) were referred late. Advice is mainly health workers midwife or health centers are expected to more concerned about pregnant through antenatal surveillance and maternal and delivery is more sensitive to problems or indications that require immediate action and should be referred to hospital. Region governments are expected to pay more attention to public access to reach the health services and counseling efforts and training of the tradisional healer or shaman. Keyword : Family decision, fund, geographic, birth attendants, maternal referral delay, Gunungsitoli Hospital